Utilizing a Bioscaffold for Socket Preservation: A Case Report - Adhikari, Khushbu; Tandukar, A.; Kumar, B.; Khanal, B. (Journal of Nepalese Prosthodontic Society, 2018)
Socket preservation technique preserves the soft and the hard tissues after tooth extraction; hence minimizing the need for any augmentation procedures in the future. Platelet Rich Fibrin (PRF) enhances the osteogenic differentiation and the healing process so can be utilised for socket preservation. This is a case report of utilizing PRF in combination with hydroxyapatite crystals in an extracted socket, to preserve the future implant site. The tooth was extracted atraumatically and the socket was thoroughly debrided. Venous blood was collected from the patient’s antecubital fossa and PRF was prepared immediately by centrifuging the collected blood at 3000 rpm for 10 minutes. A mixture of hydroxyapatite and PRF was placed in the socket; covered by a PRF membrane and sutured with 3-0 silk suture. The radiographic and clinical evaluation demonstrated satisfactory regeneration of bone and soft tissue. Socket preservation technique using PRF and hydroxyapatite is an effective method for achieving sound bone and tissue for implant placement.